Catalytic Activation of Imines by Chalcogen Bond Donors in a Povarov [4+2] Cycloaddition Reaction. Issue 47 (12th July 2022) - Steinke, Tim; Wonner, Patrick; Gauld, Richard M.; Heinrich, Sascha; Huber, Stefan M.
Abstract: Recently, chalcogen bonding has been investigated in more detail in organocatalysis and the scope of activated functionalities continues to increase. Herein, the activation of imines in a Povarov [4+2] cycloaddition reaction with bidentate cationic chalcogen bond donors is presented. Tellurium‐based Lewis acids show superior properties compared to selenium‐based catalysts and inactive sulfur‐based analogues. The catalytic activity of the chalcogen bonding donors increases with weaker binding anions. Triflate, however, is not suitable due to its participation in the catalytic pathway. A solvent screening revealed a more efficient activation in less polar solvents and a pronounced effect of solvent (and catalyst) on endo : exo diastereomeric ratio. Finally, new chiral chalcogen bonding catalysts were applied but provided only racemic mixtures of the product. Abstract : Tellurium‐based chalcogen bonding catalysts successfully activate a Povarov [4+2] cycloaddition with catalyst loadings as low as 1 mol %, with different substrates, and in different solvents. Furthermore, new chiral chalcogen bonding catalysts were introduced and tested in this reaction, but only racemic mixtures of the product were obtained.